Problematika Beragama di Indonesia: Potret Persepsi Masyarakat Terhadap Otoritas Fatwa Majelis Ulama Indonesia - Author: Rohidin (Jurnal Hukum IUS QUIA IUSTUM, 2011)
This study focused on the assessment of public perception on fatwa of The Council of Indonesian ‘Ulama’ (MUI) about the religious cult in Indonesia who has become quite intense public debate. Various responses to that fatwa, on the one side create a religious life in Indonesia more dynamic, but on the other side, the public misunderstanding to the status of a fatwa making religious life became disturbed. This research included in the qualitative research tradition. The main characteristic of this research is the way of observation and data collection performed in the background or natural setting, Based on the results of research in the field, the public perception on fatwa of The Council of Indonesian‘Ulama’ (MUI) inferential into three views: First, exclusive category, those in support to the fatwa with all the consequences (taken for granted). Second, inclusive-moderate category, those in support to the fatwa with record does not affect to the civil rights who has been deceive. Third, inclusive-extreme category, those who refuse for any reason (apriori).Key words : Religious problems, public perception, fatwa authority